QUANTITATIVE EASING OF MONETARY POLICY AND ITS MANIFESTATIONS IN THE FIXED INCOME SEGMENT - Jakl, Jakub; Brůna, Karel, 1973-; Tůma, Zdeněk, 1960-; Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví (2019)
This dissertation thesis is devoted to the topic of Quantitative Easing (QE) of monetary policy and consists from four academic papers that deal with the quantitative easing and its manifestations, mainly in the fixed income segment, in the U.S. and the Eurozone economy.The first paper focuses on the QE episode undertaken by the Federal Reserve System in the U.S. and its effects on assets prices, mainly on QE-targeted assets and its investment alternatives using event study and VAR analysis. In this paper a non-negligible impact of QE on purchased assets was found in both models through all waves of QE and time persistency patterns in VAR impulse-response functions (IRFs) part. Furthermore, some evidence for portfolio-balance and other related effects was found.The second paper focuses on analysis of possible effects of the ECB’s Public sector purchase programme (PSPP) on portfolios of the Eurozone investors. This paper incorporates the counterfactual analysis approach and uses sectoral data regression analysis of asset holdings of different investors in the Eurozone. The series of obtained regression estimates and counterfactual analysis graphic representation identified a nonnegligible effect of the PSPP on the rebalancing of government bond portfolios towards riskier corporate bonds and equities across investor types in major Eurozone countries.The third paper focuses on the effects of the ECB's Corporate sector purchase programme (CSPP) on yields of corporate sector bonds and its impact on corporate sector debt markets. Detailed regression-controlled event study focused on relevant events and impulse-response analysis of constructed VAR models were used to obtain series of sector-specific and country-specific results. Results showed non-negligible impact of the CSPP on purchased bonds in both models.
Size and persistency of stock and flow effects of ECB's actions were considerably different in various segments of the Eurozone corporate bond market. Furthermore, detailed representative-company based analysis in main Eurozone countries gives us microeconomic quantification of the real change of funding costs induced by the CSPP.The fourth, and final, paper focuses on the identification and quantification of possible effects of the ECB’s asset purchase programmes (APPs) on the SER spread, while the main focus is given to detailed intraday analysis of the implementation of the Public Sector Purchase Programme (PSPP). High frequency intraday approach analysis was also implemented in order to identify which leg of the SER spread was decisive in determining the SER spread change in the first three years of the PSPP implementation. Whether it was the “sovereign bond-based leg” directly affected by the ECB’s PSPP purchases or the “interbank lending / STIR-based leg”. The central finding is that the bond-based leg was the SER spread determining leg since the beginning (or even since the anchoring of market anticipation) of the PSPP programme and this role even intensified later on in 2016/2017 when the squeeze on prime bond markets hit hard its yields.The introductory chapter summarizes the theoretical background of QE monetary policy and put papers constituent to this thesis into a wider context. The final chapter summarizes the papers results and overall benefits of this dissertation thesis for monetary theory and practice.
Vedoucí práce: Karel Brůna
Disertační práce (Ph.D.)—Vysoká škola ekonomická v Praze. Fakulta financí a účetnictví, 2019
Obsahuje bibliografii
Textový (vysokoškolská kvalifikační práce)
Rok obhajoby 2019
Způsob přístupu: Internet
Keywords: finance [obor disert. práce]; disertace; dissertations